THE USE OF SEMANTIC MAPPING TO INCREASE STUDENTS VOCABULARY AT THE SECOND GRADE STUDENTS OF SMPN 9 MATARAM IN ACADEMIC YEAR 2014/2015 - HIDAYATI HIDAYATI; RUSNAINI RUSNAINI (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2016)
Semantic mapping is introduced as a vocabulary presentation technique. The purpose of this research is to know the effectiveness of using semantic mapping indeveloping students’ vocabulary to the second year students’ of SMPN 9 Mataram in Academic year 2014/2015. The population of the study was the second year students of SMPN 9 Mataram, there are six classes and every class consist of 26 students’, so, the total number of the population were 180 students, and the researcher only took one class is VIII A, with consist of 26 students.This study is kind of pre-experimental in research designed pretest-posttest group, using a measurement technique in form of multiple choicesand semantic mapping which consist of 30 test items. Based on the data analysis the mean score of pre-test 39, qualifying “POOR” and mean score ofpost-test88 qualifying average to “GOOD”, and the result of t -test that is 45,6. Based on the distribution t-table with db=26, the research showed the distribution t-table was 99 % trust interval and level of significant 1%. And the result confirmed that the using of semantic mappingtechnique in teaching vocabulary at the eight class students is effective in increasing student’s vocabulary mastery.